Environmental and Economic Development of the Arctic Zone of the Russian Federation: on the Evolution of the System of External and Internal Challenges - V. A. Shamakhov; N. M. Mezhevich (Управленческое консультирование)
The article addresses the issues of foreign policy risks related to environmental problems in the Russian Arctic. It is shown that at the turn of 2019 a new system of external challenges to the Russian development of the Arctic was formed. Desuverenization will progress through environmental requirements. An adequate system of Russian response to these risks is needed. At the same time, increased attention to the environmental aspects of economic activity will prevent attempts to intercept management.